Answer:
<h2>
CYLINDER</h2>
Surface Area = 471.2 cm^2
<h2>
TRIANGULAR PRISM</h2>
Surface Area = 60.75 m^2
Step-by-step explanation:
<h2>
CYLINDER</h2>
The surface area formula for a cylinder is π x diameter x (diameter / 2 + height), where (diameter / 2) is the radius of the base (d = 2 x r), so another way to write it is π x radius x 2 x (radius + height). ( π =3.14 )
FORMULA:
π x 5 x 2 x 15
WORK:
π x 5 = 15.7
15.7 x 2 = 31.4
31.4 x 15 = 471
<h2>
TRIANGULAR PRISM</h2>
The surface area formula for a triangular prism is 2 * (height x base / 2) + length x width1 + length x width2 + length x base.
FORMULA:
2 x (2.5 x 1.5/2) + (6 x 4) + (6 x 4) + (6 x 1.5)
WORK:
(2.5 x 1.5) = 3.75/2 = 1.875
1.875 x 2 = 3.75
(6 x 4) = 24
(6 x 4) = 24
(6 x 1.5) = 9
3.75 + 24 + 24 + 9 = 60.75
Other ways are m<1, YFP and m<F.
The angle is an acute angle because it is less than a right angle (less than 90 degrees).
First find the perimeter of the rectangle: 2w+2l which is 8+28=36. Then find the square root of 36 which is 6 so that is the answer.
Answer:
x³ - (√2)x² + 49x - 49√2
Step-by-step explanation:
If one root is -7i, another root must be 7i. You can't just have one root with i. The other roos is √2, so there are 3 roots.
x = -7i is one root,
(x + 7i) = 0 is the factor
x = 7i is one root
(x - 7i) = 0 is the factor
x = √2 is one root
(x - √2) = 0 is the factor
So the factors are...
(x + 7i)(x - 7i)(x - √2) = 0
Multiply these out to find the polynomial...
(x + 7i)(x - 7i) = x² + 7i - 7i - 49i²
Which simplifies to
x² - 49i² since i² = -1 , we have
x² - 49(-1)
x² + 49
Now we have...
(x² + 49)(x - √2) = 0
Now foil this out...
x²(x) - x²(-√2) + 49(x) + 49(-√2) = 0
x³ + (√2)x² + 49x - 49√2